2004
DOI: 10.1162/1088198041269481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Land‐Use Impacts: Selection of Surface Area Metrics for Life‐Cycle Assessment of Mining

Abstract: Keywords environmental performance measurement equivalency factors land-use metrics life-cycle assessment (LCA) life-cycle impact assessment (LCIA) mining e-supplement available on the JIE Web site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…In spite of the low application of life cycle thinking to decision making in the mining industry, some examples of mining LCA studies can be found in the literature (Awuah-Offei et al 2008a, b;Bovea et al 2007;Durucan et al 2006;Mangena and Brent 2006;Spitzley and Tolle 2004;Suppen et al 2006). The goals of these LCAs vary and include estimating land-use equivalency factors (Spitzley and Tolle 2004), identifying high impact processes during mining, treating and marketing of red clay (Bovea et al 2007), evaluating the life cycle environmental impacts of different grades of coal mined with different mining methods (Mangena and Brent 2006), and life cycle environmental impact assessment of mine haulage options in surface mines (Awuah-Offei et al 2008a).…”
Section: Current Lca Applications In Miningmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of the low application of life cycle thinking to decision making in the mining industry, some examples of mining LCA studies can be found in the literature (Awuah-Offei et al 2008a, b;Bovea et al 2007;Durucan et al 2006;Mangena and Brent 2006;Spitzley and Tolle 2004;Suppen et al 2006). The goals of these LCAs vary and include estimating land-use equivalency factors (Spitzley and Tolle 2004), identifying high impact processes during mining, treating and marketing of red clay (Bovea et al 2007), evaluating the life cycle environmental impacts of different grades of coal mined with different mining methods (Mangena and Brent 2006), and life cycle environmental impact assessment of mine haulage options in surface mines (Awuah-Offei et al 2008a).…”
Section: Current Lca Applications In Miningmentioning
confidence: 99%
“…The goals of these LCAs vary and include estimating land-use equivalency factors (Spitzley and Tolle 2004), identifying high impact processes during mining, treating and marketing of red clay (Bovea et al 2007), evaluating the life cycle environmental impacts of different grades of coal mined with different mining methods (Mangena and Brent 2006), and life cycle environmental impact assessment of mine haulage options in surface mines (Awuah-Offei et al 2008a). The diversity of the motivation behind these studies shows the versatility of the LCA methodology and its potential in the mining industry.…”
Section: Current Lca Applications In Miningmentioning
confidence: 99%
See 3 more Smart Citations